Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1371/journal.pone.0178575
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diversity and frequency of the diarrheagenic enteric protozoan Giardia duodenalis and Cryptosporidium spp. in a hospital setting in Northern Spain

Abstract: BackgroundHuman giardiosis and cryptosporidiosis are caused by the enteric protozoan parasites Giardia duodenalis and Cryptosporidium spp. Both pathogens are major contributors to the global burden of diarrhoeal disease, affecting primarily children and immunodebilitated individuals in resource-poor settings. Giardiosis and cryptosporidiosis also represent an important, often underestimate, public health threat in developed countries. In Spain only limited information is currently available on the epidemiology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 61 publications
4
27
2
Order By: Relevance
“…Similar results were obtained 15 . However, the results did not reveal mixed groups A and B 16 . High genetic variability and the frequency of double peaks make sub-genotyping problematic.…”
Section: Abbreviations Listmentioning
confidence: 57%
“…Similar results were obtained 15 . However, the results did not reveal mixed groups A and B 16 . High genetic variability and the frequency of double peaks make sub-genotyping problematic.…”
Section: Abbreviations Listmentioning
confidence: 57%
“…Even more intriguing was the fact that three out of the four C. hominis sequences generated at the ssu rRNA locus corresponded to genetic variants of the parasite not described previously, whereas the fourth one was identified as a genotype commonly seen in Spanish clinical patients (e.g. GenBank accession number KY499055) (Azcona‐Gutiérrez et al., 2017; de Lucio et al., 2016). Such variety of distinct, novel sequences may be indicative of true C. hominis infections rather than accidental carriage (spurious infection) of ingested oocysts of the parasite.…”
Section: Discussionmentioning
confidence: 93%
“…Analysis of the sequences obtained at the gdh locus allowed the identification of sub-assemblage AII and discordant genotype BIII/BIV results in 5 (62.5%) and 3 (37.5%) isolates, respectively. Azcona-Gutierrez et al (2017) genotyped 90 human isolates of G. duodenalis at the gdh and bg genes, reporting discordant genotyping results in one (6%) isolate [54]. In another study conducted by Skhal et al (2017) discordant genotype results BIII/BIV were reported in four (10%) isolates [55].…”
Section: Discussionmentioning
confidence: 99%